Construction of Six‐Oxygen‐Coordinated Single Ni Sites on g‐C3N4 with Boron‐Oxo Species for Photocatalytic Water‐Activation‐Induced CO2 Reduction. Issue 48 (27th September 2021) - Wang, Yuying; Qu, Yang; Qu, Binhong; Bai, Linlu; Liu, Yang; Yang, Zhao‐Di; Zhang, Wei; Jing, Liqiang; Fu, Honggang
Abstract: The configuration regulation of single‐atom photocatalysts (SAPCs) can significantly influence the interfacial charge transfer and subsequent catalytic process. The construction of conventional SAPCs for aqueous CO2 reduction is mainly devoted toward favorable activation and photoreduction of CO2, however, the role of water is frequently neglected. In this work, single Ni atoms are successfully anchored by boron‐oxo species on g‐C3 N4 nanosheets through a facile ion‐exchange method. The dative interaction between the B atom and the sp 2 N atom of g‐C3 N4 guarantees the high dispersion of boron‐oxo species, where O atoms coordinate with single Ni (II) sites to obtain a unique six‐oxygen‐coordinated configuration. The optimized single‐atom Ni photocatalyst, rivaling Pt‐modified g‐C3 N4 nanosheets, provides excellent CO2 reduction rate with CO and CH4 as products. Quasi‐in‐situ X‐ray photoelectron spectra, transient absorption spectra, isotopic labeling, and in situ Fourier transform infrared spectra reveal that as‐fabricated six‐oxygen‐coordinated single Ni (II) sites can effectively capture the photoelectrons of CN along the BO bridges and preferentially activate adsorbed water to produce H atoms to eventually induce a hydrogen‐assisted CO2 reduction. This work diversifies the synthetic strategies for single‐atom catalysts and provides insight on correlation between the single‐atom configuration and reaction pathway. Abstract : Six‐oxygen‐coordinated single Ni (II) sites are successfully anchored by highly dispersed boron‐oxo species on g‐C3 N4 nanosheets. The as‐fabricated single‐atom Ni photocatalyst can realize efficient photocatalytic CO2 reduction, where single Ni atoms can effectively capture photoelectrons and preferentially reduce absorbed water to produce H atoms as active species eventually inducing the reduction of CO2 .